Gender Issues in Comfort Woman by Nora Okja Keller (American & British Studies Annual, 2023)
Through an exploration of the comfort women system, this article analyzes how the female gender has been oppressed in history. It follows the story of Akiko, the main character of Comfort Woman (1998) by Asian American author Nora Okja Keller. Keller is one of the first authors to write about comfort women, gaining publicity for this issue. This article provides an examination of terms such as sex, gender, and gender issues. Certain concepts influencing American and Asian cultures and their stance towards gender are also analyzed, after which focus is placed on the portrayal of gender roles as illustrated in the novel. The article briefly mentions the history of the relationship between the United States and Korea. The characteristics of the comfort women system are described as well as the causes leading to its establishment such as patriarchy, Confucian traditions, and the exploitability of lower-class society. Additionally, the article highlights how the comfort women issue helped define feminist theory in the US and identifies the transnational nature of the issues involved.
Keywords: Nora Okja Keller; Comfort Woman; comfort women system; gender; Second World War